Enhancing Pharmacy Students Speaking Proficiency: A Comparative Study of “MOOCs” and “ABSYAK Online Media” in English Language Learning - Syakur, Abd.; Sugirin, Sugirin; Margana, Margana; Prasetya, Rizki; Prawoco, Fajar Sandi; Surono, Yan (Journal of Posthumanism, 2025)
E-learning has gained widespread popularity as a key educational tool in higher education institutions, with platforms such as Massive Open Online Courses (MOOCs) being explored for their potential to replace or complement traditional classroom instruction. Despite extensive studies on e-learning platforms, limited attention has been given to student perceptions, particularly in specialized fields like pharmacy education. This study investigates the effectiveness of MOOCs and the locally developed “Absyak Online Media” (AOM) in enhancing English speaking skills among pharmacy students. Conducted at the Pharmacy Academy of Surabaya, East Java, the study involved 60 participants and employed a mixed-method approach combining qualitative interviews and quantitative analysis. Findings indicate that AOM significantly outperforms MOOCs in three key areas: learning attributes (AOM: 36.95 > MOOCs: 27.13), learning process (AOM: 36.88 > MOOCs: 27.17), and student preferences (AOM: 45.05 > MOOCs: 33.48). Students favored AOM for its engaging multimedia features—including interactive videos, PowerPoint materials, and pharmaceutical-focused YouTube content—which effectively supported speaking skill development. These results suggest that tailored online media like AOM may offer greater benefits than generic MOOCs for language instruction in domain-specific contexts. The findings have important implications for educators, instructional designers, and developers of e-learning platforms.